Chasing for water monitors using dogs in West Java, Indonesia: a recreational hunting or pest control? - Prima Yudha, Andhika; Dikari Kusrini, Mirza; Arida, Evy (Ethnobiology and Conservation, 2022)
Wildlife hunting for subsistence is mostly reported in rural areas and performed by traditional people. Whereas it is also practiced in urban areas and targeted for abundant urban species such as the. water monitor (Varanus salvator). Urban hunting may be linked to pest control or pastime activity, which could be beneficial for wildlife management. Our purpose of study was to investigate hunting practice of water monitor in Bogor area, West Java, Indonesia. Data was collected between January and June 2020 to find characteristics and motivation of hunters, their hunting methods, and harvests. We were able to conduct face-to-face interviews with 42 local urban people, whom we followed in four hunting groups during their search for wildlife. Generally, hunters were students, workers, or laborers, who hunt only during the weekends. To capture water monitors, some hunters used dogs and air rifles, while some others used nothing but bare hands. During our observation, 157 individual water monitors were targeted, but only 150 were caught. There were several motivations for hunters to target water monitors apart from being a hobby, i.e., for food and to eliminate pest. Due to its motivation and strategy, we consider the hunt for water monitor in Bogor area mainly for recreational purposes.